Endoplasmic reticulum stress-related CLIP4 plays a procarcinogenic role in hepatocellular carcinoma: an integrated analysis - Anqi Wang; Sitong Yan; Weijia Jiang; Xiang Chen; Yuhan Huang; Xiangyu Zu; Xiao Du; Lulu Fan; Jiatao Liu; Guoping Sun (BMC Cancer)
Abstract Objective To explore the potential of endoplasmic reticulum stress (ERS)-associated protein CLIP4 as a biomarker for hepatocellular carcinoma (HCC) and the underlying mechanism. Methods TCGA public database and a tissue microarray were used to investigate the molecular characteristics of CLIP4 and its association with disease. TCGA-LIHC dataset was used for single-gene differential expression analysis, single-gene correlation analysis, functional enrichment analysis, immune infiltration analysis, and DNA methylation analysis. RNA-seq, immunohistochemistry, western blotting, and RT-qPCR were used to verify the effect of ERS on CLIP4 expression. Public databases and miRNA-seq data were used to explore the TF-miRNA-CLIP4 regulatory network. CCK-8, colony formation, EdU staining, wound-healing, Transwell, western blotting and RT-qPCR were used to detect the effects of CLIP4 on the proliferation, migration and epithelial-mesenchymal transition (EMT) of HCC cells. Results Analysis of TCGA datasets and tissue microarrays demonstrated that elevated CLIP4 expression was associated with poor prognosis in HCC. Enrichment analysis revealed that CLIP4 is involved in the immune response, cell adhesion, and EMT. There was a positive correlation between CLIP4 expression and the infiltration of the majority of immune cells, immunomodulators, and chemokines. Furthermore, the DNA methylation pattern of CLIP4 was found to have significant prognostic value. ERS was found to significantly upregulate CLIP4 expression. In addition, the ERS-RELA-miR-222-5p-CLIP4 transcriptional network was constructed to clarify the role of CLIP4. Cell function experiments confirmed that it promotes the proliferation, migration, and EMT of HCC cells. Conclusions CLIP4 is a potential immune-related oncogenic molecule in HCC. ERS regulates the expression of CLIP4, and CLIP4 promotes the proliferation, migration, and EMT of HCC cells.